RhoA/ROCK Signaling Regulates Drp1-Mediated Mitochondrial Fission During Collective Cell Migration - Qu, Chen; Yang, Wen; Kan, Yating; Zuo, Hui; Wu, Mengqi; Zhang, Qing; Wang, Heng; Wang, Dou; Chen, Jiong (Frontiers in Cell and Developmental Biology, 2022)
Collective migration plays critical roles in developmental, physiological and pathological processes, and requires a dynamic actomyosin network for cell shape change, cell adhesion and cell-cell communication. The dynamic network of mitochondria in individual cells is regulated by mitochondrial fission and fusion, and is required for cellular processes including cell metabolism, apoptosis and cell division. But whether mitochondrial dynamics interplays with and regulates actomyosin dynamics during collective migration is not clear. Here, we demonstrate that proper regulation of mitochondrial dynamics is critical for collective migration of Drosophila border cells during oogenesis, and misregulation of fission or fusion results in reduction of ATP levels. Specifically, Drp1 is genetically required for border cell migration, and Drp1-mediated mitochondrial fission promotes formation of leading protrusion, likely through its regulation of ATP levels. Reduction of ATP levels by drug treatment also affects protrusion formation as well as actomyosin dynamics. Importantly, we find that RhoA/ROCK signaling, which is essential for actin and myosin dynamics during border cell migration, could exert its effect on mitochondrial fission through regulating Drp1’s recruitment to mitochondria. These findings suggest that RhoA/ROCK signaling may couple or coordinate actomyosin dynamics with mitochondrial dynamics to achieve optimal actomyosin function, leading to protrusive and migratory behavior.